TAFSIR MODERAT KONSEP JIHAD DALAM PERSPEKTIF M. QURAISH SHIHAB - Thoriqul Aziz & Ahmad Zainal Abidin (IAIN Tulungagung, 2017)
Jihad was often misinterpreted by some groups. The radical group understands jihad only as the extent of the physical warfare of arms; while liberal one understands jihad only as fighting against the passions and temptations of Satan to deny another form and meaning of jihad. Jihad should be interpreted in accordance with the context. Among the interpretations from these groups appear moderate group. One of the tafsir works of jihad with the moderate character was Tafsir al-Mishbah by M. Quraish Shihab. This study found: (1) the meaning of jihad was to devote all the abilities/to bear sacrifices and truth. Those two meanings included: a) the object and target of jihad, includingjihad against lust, jihad against satan, jihad against unbelievers, against thepolytheist and jihad against the hypocrites, b) the means of jihad, encompassingjihad which appropriate with the circumstances of the development of scienceand technology, jihad with property, jihad with the soul, the jihad with energy,jihad with the mind , jihad with heart, jihad with oral, jihad with writing,jihad with emotion, jihad with al-Qur’an, jihad with war (taking up arms),jihad with time, and jihad with knowledge, c) forms of jihad, including: jihadof scientist with the use of his knowledge, of employee with his or her goodwork, of teachers with their perfect teaching, of the leaders with their justice,of the businessman with his honest, of the gun carrier with the conquest ofthe oppressive enemies. (2) the interpretation of jihad by M. Quraish Shihab found its relevance in Indonesia. Jihad in Indonesia would be directed to jihad in the social, education and economic fields.